Does the Bleaching Gel Application Site Interfere With the Whitening Result? A Randomized Clinical Trial - Esteves, Lmb [UNESP]; Fagundes, Ticiane Cestari [UNESP]; Santos, Paulo Henrique dos [UNESP]; Silva, Lmav da [UNESP]; Alcântara, S. de [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Briso, André Luiz Fraga [UNESP] (Operative Dentistry, 2022)
This study aimed to evaluate the effect of the bleaching gel application site on chromatic changes and postoperative sensitivity in teeth. Thirty patients were selected and allocated to three groups (n=10 per group), according to the location of the gel: GI, cervical application; GII, incisal application; and GIII, total facial. The amount and time of application of the 35% hydrogen peroxide (H2O2) gel were standardized. Color changes were analyzed by ΔE and Wid (bleaching index), using the values obtained in the readings conducted on a digital spectrophotometer in the cervical (CRs) and incisal regions (IRs) of the teeth. Spontaneous sensitivity was assessed using the questionnaire, and the stimulated sensitivity caused by the thermosensory analysis (TSA). The analysis occurred in five stages: baseline, after the first, second, and third whitening sessions (S), and 14 days after the end of the whitening, using the linear regression statistical model with mixed effects and post-test by orthogonal contrasts (p<0.05). Although the IR was momentarily favored, at the end of the treatment, the restriction of the application site provided results similar to those obtained when the gel was applied over the entire facial surface. Regarding sensitivity, only the GI showed spontaneous sensitivity. In the TSA, GIII had less influence on the threshold of the thermal sensation. It was concluded that the chromatic alteration does not depend on the gel application site. Spontaneous sensitivity is greater when the gel is concentrated in the cervical region (CR), and the teeth remain sensitized by thermal stimuli even after 14 days.